Amelioration of Endotoxemia by a Synthetic Analog of Omega-3 Epoxyeicosanoids - Shikuma, Akira; Kami, Daisuke; Maeda, Ryotaro; Suzuki, Yosuke; Sano, Arata; Taya, Toshihiko; Ogata, Takehiro; Konkel, Anne; Matoba, Satoaki; Schunck, Wolf-Hagen; Gojo, Satoshi (Frontiers in Immunology, 2022)
Sepsis, a systemic inflammatory response to pathogenic factors, is a difficult to treat life-threatening condition associated with cytokine and eicosanoid storms and multi-organ damage. Omega-3 polyunsaturated fatty acids, such as eicosapentaenoic (EPA) and docosahexaenoic acid, are the precursors of potent anti-inflammatory lipid mediators, including 17,18-epoxyeicosatetraenoic acid (17,18-EEQ), the main metabolite of EPA generated by cytochrome P450 epoxygenases. Searching for novel therapeutic or preventative agents in sepsis, we tested a metabolically robust synthetic analog of 17,18-EEQ (EEQ-A) for its ability to reduce mortality, organ damage, and pro-inflammatory cytokine transcript level in a mouse model of lipopolysaccharide (LPS)-induced endotoxemia, which is closely related to sepsis. Overall survival significantly improved following preventative EEQ-A administration along with decreased transcript level of pro-inflammatory cytokines. On the other hand, the therapeutic protocol was effective in improving survival at 48 hours but insignificant at 72 hours. Histopathological analyses showed significant reductions in hemorrhagic and necrotic damage and infiltration in the liver. In vitro studies with THP-1 and U937 cells showed EEQ-A mediated repression of LPS-induced M1 polarization and enhancement of IL-4-induced M2 polarization of macrophages. Moreover, EEQ-A attenuated the LPS-induced decline of mitochondrial function in THP-1 cells, as indicated by increased basal respiration and ATP production as well as reduction of the metabolic shift to glycolysis. Taken together, these data demonstrate that EEQ-A has potent anti-inflammatory and immunomodulatory properties that may support therapeutic strategies for ameliorating the endotoxemia.